Implementation of Teaching Factory in Improving the Expertise Competence of Culinary Department Students at SMKN 1 Sikur - Huldiya Syamsiar; Elmi Rahadi; M. Lutfi; Siti Rabiatul Adawiyah; Miya Witri Syafa; Lilis Sri Wahyuni; Latifatuz Zuhro; Rinayatul Aini; Munzirol Hasanati; Iswari Komalasari; Suhartiwi Suhartiwi; Yeni Maulida (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
The purpose of this study was to determine how the implementation of the Teaching Factory applied at SMK Negeri 1 Sikur can have an impact on improving the competency of culinary students. This study uses a descriptive qualitative method with the research subjects being the head of the TeFa committee and culinary students at SMK Negeri 1 Sikur. In collecting data, this study used interview, observation, and documentation techniques. Meanwhile, the data processing technique used in the study was data analysis using the Miles & Huberman model, including: data collection, data reduction, data presentation, and drawing conclusions. The results obtained from the study were a significant positive impact on students' competency. This can be seen from the increase in the average score of student competency tests, the number of awards won in student skills competitions (LKS) at regional and national levels, increased competitiveness of graduates in the world of work, development of entrepreneurial spirit in students, increasing interest in culinary majors at SMK Negeri 1 Sikur, and increasing cooperation with industry partners.